Method for preparing solid electrolyte membrane by using phase inversion method
The preparation of solid electrolyte membranes through the phase inversion method solves the problems of complex processes, high costs and difficult to control microstructure in traditional methods, achieves efficient and low-cost membrane preparation, improves electrochemical performance and mechanical strength, and meets the needs of solid-state batteries. meet high performance requirements and are environmentally friendly.
Patent Information
- Application Number
- CN202411575592.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-24
AI Technical Summary
The preparation method of traditional solid electrolyte membranes has problems such as complex process, high cost, and difficulty in controlling microstructure, resulting in low conductivity, large interface resistance, and insufficient mechanical strength, limiting the application range of solid-state batteries.
The solid electrolyte membrane is prepared using the phase inversion method. Through carefully designed raw material ratio and process conditions, including preparation of precursor solution, preparation of desolvated porous membrane by phase inversion method and pressing heat treatment, it has excellent electrochemical properties and mechanical strength. solid electrolyte membrane.
The efficient and low -cost preparation of solid -state electrolytes is realized, the electrochemical performance and mechanical strength of the membrane is improved, the solid battery requirements for high -performance electrolytes are met, and they have the characteristics of environmental protection and friendship.
Smart Images

Figure CN119361843A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of energy storage technology, and in particular to a method for preparing a solid electrolyte membrane by using a phase conversion method. Background Art
[0002] With the growing demand for high energy density and long life batteries in new energy vehicles, wearable devices and other fields, solid-state batteries have become a hot topic of research due to their high safety and wide operating temperature range. However, as the core component of solid-state batteries, the performance of solid electrolyte membranes directly affects the overall performance of the battery.
[0003] Traditional solid-state electrolyte membrane preparation methods, such as sol-gel method and casting method, often have disadvantages such as complex preparation process, high cost, and difficulty in controlling the microstructure, resulting in low electrical conductivity, large interface resistance, and insufficient mechanical strength of the electrolyte membrane, limiting the application scope of solid-state batteries.
[0004] Phase inversion is an advanced membrane preparation technology that can form membrane materials with specific porous structures through the exchange between solvent and non-solvent. This method has the advantages of simple process, easy control of membrane structure, and low cost, and has been widely used in water treatment, gas separation and other fields. Applying the phase inversion method to the preparation of solid electrolyte membranes can not only simplify the preparation process and reduce production costs, but also optimize the electrochemical properties and mechanical strength of the electrolyte membrane by regulating the porous structure. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a solid electrolyte membrane using a phase inversion method, and the efficient preparation of the electrolyte membrane is achieved through the carefully designed raw material ratio and process conditions. The prepared solid electrolyte membrane not only has excellent electrochemical properties, such as high ionic conductivity, low interface resistance, etc., which can meet the high performance requirements of solid-state batteries for electrolyte membranes, but also has environmentally friendly characteristics and conforms to the concept of sustainable development.
[0006] To achieve the above object, the present invention provides a method for preparing a solid electrolyte membrane using a phase inversion method, comprising the following steps: S1. Prepare raw materials to prepare precursor solution; S2, preparing a desolvated porous membrane by phase inversion method; S3. The desolvated porous membrane is subjected to pressing and heat treatment to obtain a solid electrolyte membrane.
[0007] Preferably, the raw materials in S1 include solid electrolyte powder and inorganic ceramic particles. The solid electrolyte powder and inorganic ceramic particles are dissolved in a solvent, stirred evenly, and then heated and stirred to obtain a precursor solution.
[0008] Preferably, the solid electrolyte powder includes one or more of vinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polyethylene oxide, polymethyl methacrylate, polyether sulfone and thermoplastic polyurethane elastomer.
[0009] Preferably, the inorganic ceramic particles include one or more of lithium aluminum titanium phosphate, LAGP, garnet-type solid electrolyte, LLZTO and LGPS.
[0010] Preferably, the amount of inorganic ceramic particles used is 10-30% of the total mass of the solid electrolyte powder.
[0011] Preferably, the solvent includes one of N,N-dimethylformamide, N-methylpyrrolidone and acetonitrile.
[0012] Preferably, the heating and stirring temperature in S1 is 40-60° C., and the heating and stirring time is 3-6 h.
[0013] Preferably, the specific operation of S2 is: coating the precursor solution on a polytetrafluoroethylene plate or a glass plate by a scraper, and then placing it in a non-solvent and allowing it to stand to form a desolvated porous membrane.
[0014] Preferably, the non-solvent in S2 includes one of deionized water and ethanol, and the standing time in S2 is 3-5 minutes.
[0015] Preferably, the heat treatment in S3 is drying in a vacuum drying oven at 40-60° C. for 8-12 hours.
[0016] Therefore, the present invention adopts the above-mentioned method for preparing a solid electrolyte membrane using a phase inversion method, which has the following beneficial effects: (1) By precisely controlling the raw material ratio and process conditions, efficient and low-cost preparation of solid electrolyte membranes is achieved.
[0017] (2) The prepared solid electrolyte membrane has a porous structure, which is conducive to the rapid transport of ions, thereby improving the electrochemical performance of the membrane.
[0018] (3) The pressing process enhances the mechanical strength and density of the membrane, ensuring the long-term stable operation of the battery.
[0019] (4) This method is simple, environmentally friendly, and reduces production costs, providing strong support for the large-scale commercial application of solid-state batteries.
[0020] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1is a SEM image of the surface and interface of a solid electrolyte membrane in an embodiment of a method for preparing a solid electrolyte membrane using a phase inversion method of the present invention; Figure 2 The Nyquist curve, the DC polarization curve and the electrochemical window curve of the solid electrolyte membrane of an embodiment of the method for preparing a solid electrolyte membrane by using a phase inversion method of the present invention; Figure 3 The specific discharge capacity of a solid-state battery at different current densities at 25° C. in an embodiment of a method for preparing a solid-state electrolyte membrane using a phase inversion method of the present invention; Figure 4 It is the discharge specific capacity of an embodiment of a method for preparing a solid electrolyte membrane using a phase inversion method of the present invention after 200 cycles at a current density of 1C. DETAILED DESCRIPTION
[0022] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0023] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0024] Example The present invention provides a method for preparing a solid electrolyte membrane using a phase inversion method, comprising the following steps: S1. Prepare raw materials for precursor solution. The raw materials include solid electrolyte powder and inorganic ceramic particles. Dissolve 1-3g of solid electrolyte powder and inorganic ceramic particles (10-30% of the total mass of solid electrolyte powder) in a solvent, stir evenly, and heat and stir at 40-60°C for 3-6h to obtain a precursor solution.
[0025] The solid electrolyte powder includes one or more of vinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polyethylene oxide, polymethyl methacrylate, polyether sulfone and thermoplastic polyurethane elastomer. The inorganic ceramic particles include one or more of lithium aluminum titanium phosphate, LAGP, garnet-type solid electrolyte, LLZTO and LGPS, and the amount of the inorganic ceramic particles is 10-30% of the total mass of the solid electrolyte powder. The solvent includes one of N, N-dimethylformamide, N-methylpyrrolidone and acetonitrile.
[0026] The active ingredients in the solid electrolyte powder can form a continuous ion conduction network, ensuring that lithium ions or other carriers can be efficiently transferred between electrodes. This is one of the key factors for solid-state batteries to achieve high ionic conductivity. By adding an appropriate amount of solid electrolyte powder, the mechanical properties of the final membrane, such as toughness and tensile strength, can be improved, making it more durable and less prone to breakage. This is very important to ensure the long-term stable operation of the battery. During the phase transformation process, different types and proportions of solid electrolytes will affect the microscopic pore distribution after film formation. Appropriate regulation of these parameters helps to obtain a porous structure with suitable pore size and connectivity, which is beneficial to improving the electrolyte permeability and ion migration rate.
[0027] Inorganic ceramic particles usually have high hardness and strength, so they can significantly improve the mechanical stability of the final membrane material, such as tensile strength and puncture resistance. This is very important for preventing damage to the battery due to external forces during assembly and use. Ceramic materials have good high temperature resistance. The addition of inorganic ceramic particles can make the prepared solid electrolyte membrane have better thermal stability, thereby broadening the operating temperature range of the battery and improving safety. By controlling the type, particle size and dispersion of inorganic ceramic particles in the solution, a specific pore structure can be formed during the phase inversion process.
[0028] S2. Prepare a desolvated porous membrane by a phase inversion method; coat the precursor solution on a polytetrafluoroethylene plate or a glass plate by a scraper, then put it into deionized water or ethanol and let it stand for 3-5 minutes to form a desolvated porous membrane.
[0029] S3. The desolvated porous membrane is subjected to a pressing heat treatment to obtain a solid electrolyte membrane. The heat treatment is performed by placing the membrane in a vacuum drying oven at 40-60° C. and drying the membrane for 8-12 hours.
[0030] Embodiment 1 The present invention provides a method for preparing a solid electrolyte membrane using a phase inversion method, comprising the following steps: adding PVDF-HFP to a DMF solution, stirring evenly, and then adding LATP (10% of the total mass of the polymer matrix). The solution is heated to 40° C. and stirred for 3 hours. Then, it is poured onto a PTFE plate and evenly applied with a scraper. After scraping, the PTFE plate is immersed in deionized water. Then, the formed porous membrane is immersed in deionized water for 3 minutes to separate the remaining DMF solvent into the deionized water. The desolvated porous membrane is dried in a vacuum drying oven.
[0031] In order to verify the feasibility of the prepared solid electrolyte membrane, the morphology of the solid electrolyte membrane was observed by scanning electron microscopy (SEM); the ionic conductivity, lithium ion migration number and electrochemical window were tested using a DH-7000 electrochemical workstation; and the electrochemical performance was tested using a Xinwei battery testing system.
[0032] Figure 1 The surface and cross-sectional SEM morphology of the prepared solid electrolyte membrane. Figure 1 (a) is the surface SEM image of the solid electrolyte membrane. Figure 1 (b) in the figure is a cross-section of the solid electrolyte membrane. It can be seen from the figure that it has a porous structure with uniform pore structure.
[0033] Figure 2 (a) is the Nyquist curve of the solid electrolyte membrane. It can be concluded that the ionic conductivity of the solid electrolyte membrane is 1.2×10 -3 S / cm, and the semicircular part of the Nyquist curve is small, indicating that the impedance of the solid electrolyte membrane is low, which is beneficial to improve the conductivity and energy density of the battery. The straight line part of the Nyquist curve is long, indicating that the solid electrolyte membrane has good ion transport performance in both high and low frequency ranges, which is helpful to improve the cycle stability and safety of the battery. The shape of the Nyquist curve is stable, without obvious abnormal points, indicating that the solid electrolyte membrane is stable during the electrochemical test and has good electrochemical performance.
[0034] Figure 2 (b) in the figure is the DC polarization curve of the solid electrolyte membrane. It can be seen from the figure that the solid electrolyte membrane has a lithium ion migration number of 0.5. And in the lower potential range, the current increases rapidly with the increase of potential, indicating that the solid electrolyte membrane has good ionic conductivity. The current begins to decline after reaching the peak value, which shows that the solid electrolyte membrane has a stable electrochemical window within a certain potential range and can withstand higher potentials without obvious electrochemical reactions. The increase in current indicates that the impedance of the solid electrolyte membrane is low, which is conducive to the rapid transfer of charges. The shape of the curve shows that the solid electrolyte membrane has good stability in the electrochemical process and is not easy to decompose or degrade.
[0035] Figure 2(c) in the figure is the electrochemical window diagram of the solid electrolyte membrane. It can be seen from the figure that the solid electrolyte membrane has an electrochemical window of 4.7V, and the current remains relatively stable for a long time, indicating that the solid electrolyte membrane has good stability during long-term use. The current fluctuates less with time, indicating that the solid electrolyte membrane exhibits good electrochemical stability in the electrochemical process. The electrochemical window shown in the figure is wide, indicating that the solid electrolyte membrane can work stably in a wider potential range, which is very important for improving the performance and safety of the battery. The lower current value indicates that the leakage current of the solid electrolyte membrane is small, which helps to improve the efficiency and safety of the battery.
[0036] Figure 3 The discharge specific capacity of the solid-state battery assembled with the solid electrolyte membrane at different current densities at room temperature (25°C) shows that the solid-state battery has a high discharge specific capacity (0.1C@161.4mAh / g and 1C@117.9mAh / g). Figure 4 The discharge capacity after 200 cycles at a current density of 1C. The capacity retention rate is 89.3% after 200 cycles at 1C. The figure shows that at a current density of 1C, the discharge capacity of the battery decreases slightly during 200 cycles, but the Coulomb efficiency remains at a high level, indicating that the battery has good cycle stability and energy conversion efficiency.
[0037] Embodiment 2 The present invention provides a method for preparing a solid electrolyte membrane using a phase inversion method, comprising the following steps: adding PVDF-HFP to a DMF solution, stirring evenly, and then adding LATP (20% of the total mass of the polymer matrix). The solution is heated to 50° C. and stirred for 4 hours. Then, it is poured onto a PTFE plate and evenly applied with a scraper. After scraping, the PTFE plate is immersed in deionized water. Then, the formed porous membrane is immersed in deionized water for 4 minutes to separate the remaining DMF solvent into the deionized water. The desolvated porous membrane is dried in a vacuum drying oven.
[0038] Embodiment 3 The present invention provides a method for preparing a solid electrolyte membrane using a phase inversion method, comprising the following steps: adding PVDF-HFP to a DMF solution, stirring evenly, and then adding LATP (30% of the total mass of the polymer matrix). The solution is heated to 60° C. and stirred for 6 hours. Then, it is poured onto a PTFE plate and evenly applied with a scraper. After scraping, the PTFE plate is immersed in deionized water. Then, the formed porous membrane is immersed in deionized water for 5 minutes to separate the remaining DMF solvent into the deionized water, and the desolvated porous membrane is dried in a vacuum drying oven.
[0039] Therefore, the present invention adopts the above-mentioned method of preparing a solid electrolyte membrane using a phase inversion method, and realizes the efficient preparation of the electrolyte membrane through carefully designed raw material ratios and process conditions. The prepared solid electrolyte membrane not only has excellent electrochemical properties, such as high ionic conductivity, low interface resistance, etc., but can meet the high performance requirements of solid-state batteries for electrolyte membranes. In addition, the method is also environmentally friendly and in line with the concept of sustainable development.
[0040] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a solid electrolyte membrane using a phase inversion method, characterized in that: The following steps are involved: S1. Prepare raw materials to prepare precursor solution; S2, preparing a desolvated porous membrane by phase inversion method; S3. The desolvated porous membrane is subjected to pressing and heat treatment to obtain a solid electrolyte membrane.
2. The method for preparing a solid electrolyte membrane using a phase inversion method according to claim 1, characterized in that: The raw materials in S1 include solid electrolyte powder and inorganic ceramic particles. The solid electrolyte powder and inorganic ceramic particles are dissolved in a solvent, stirred evenly, and then heated and stirred to obtain a precursor solution.
3. The method for preparing a solid electrolyte membrane using a phase inversion method according to claim 1, characterized in that: The solid electrolyte powder includes one or more of vinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polyethylene oxide, polymethyl methacrylate, polyether sulfone and thermoplastic polyurethane elastomer.
4. The method for preparing a solid electrolyte membrane using a phase inversion method according to claim 1, characterized in that: The inorganic ceramic particles include one or more of lithium aluminum titanium phosphate, LAGP, garnet-type solid electrolyte, LLZTO, and LGPS.
5. The method for preparing a solid electrolyte membrane using a phase inversion method according to claim 1, characterized in that: The amount of inorganic ceramic particles used is 10-30% of the total mass of the solid electrolyte powder.
6. The method for preparing a solid electrolyte membrane using a phase inversion method according to claim 1, characterized in that: The solvent includes one of N,N-dimethylformamide, N-methylpyrrolidone and acetonitrile.
7. The method for preparing a solid electrolyte membrane using a phase inversion method according to claim 1, characterized in that: The heating and stirring temperature in S1 is 40-60°C, and the heating and stirring time is 3-6h.
8. The method for preparing a solid electrolyte membrane using a phase inversion method according to claim 1, characterized in that: The specific operation of S2 is: coating the precursor solution on a polytetrafluoroethylene plate or a glass plate by a scraper, and then placing it in a non-solvent and allowing it to stand to form a desolvated porous membrane.
9. The method for preparing a solid electrolyte membrane using a phase inversion method according to claim 1, characterized in that: The non-solvent in S2 includes one of deionized water and ethanol, and the standing time in S2 is 3-5 minutes.
10. The method for preparing a solid electrolyte membrane using a phase inversion method according to claim 1, characterized in that: The heat treatment in S3 is to place the mixture in a vacuum drying oven at 40-60° C. and dry it for 8-12 h.
Citation Information
Patent Citations
All-solid composite polymer electrolyte and preparation method thereof, and lithium ion battery
CN110429344A
Ion conduction organic-inorganic composite modified diaphragm as well as preparation method and application thereof
CN112670673A
Battery diaphragm, preparation method thereof and lithium ion battery
CN114824654A
Flexible composite solid electrolyte and preparation and application thereof
CN117855582A